Comparative effect of calcium supplementation on the incidence of pre-eclampsia and eclampsia among primigravid women - Carole, Assontsa Kafack; Felix, Essiben; Florence, Tumasang; Juliette, Meka Esther; Fofack, Tongo Sedrick; Enow, Mbu Robinson (Clinical Journal of Obstetrics and Gynecology, 2019)
Background: Pre-eclampsia is a frequent and serious pregnancy complication contributing for the increasing maternal morbi-mortality rates. This study was designed to evaluate the effect of calcium supplementation during pregnancy, on the incidence of pre-eclampsia and eclampsia among primigravid women. Method: In a hospital-based, opened, randomized and controlled clinical trial carried out in the city of Yaounde, 70 women were randomized to either 1.5 g daily calcium supplements (n = 35) or vitamins at the same time (n = 35) from 20 weeks gestation till delivery. Were included all singleton healthy, primigravid women who offered their signed inform consent and were excluded, all women with any chronic condition. Primary outcomes were pre-eclampsia and eclampsia. Results: No significant difference was observed between the two study groups with respect to the baseline characteristics obtained at enrollment. We recorded a sevenfold decrease in the incidence of preeclampsia in the calcium group (RR = 0.26, CI 0.06 – 0.44, p = 0.024). The onset of pre-eclampsia was delayed 3 weeks in the calcium group. Meanwhile the mean diastolic blood pressure at delivery was of no significant difference (p = 0.126), the mean systolic blood pressure at delivery however, presented a significant difference between both groups (p = 0.009). Conclusion: A 1.5 g daily calcium supplementation of healthy normotensive primigravid women during pregnancy seems to be effective in reducing the incidence of pre-eclampsia.